Enteric pathogens associated with gastroenteritis among children under 5 years in sub-Saharan Africa: a systematic review and meta-analysis. (2nd March 2020) - Oppong, T. B.; Yang, H.; Amponsem-Boateng, C.; Kyere, E. K. D; Abdulai, T.; Duan, G.; Opolot, G.
Abstract: Gastroenteritis remains a serious health condition among children under 5 years especially in Africa. We conducted a systematic review and meta-analysis to investigate the aetiologic pathogens of gastroenteritis in the region. We did a systematic search for articles with original data on the aetiology of gastroenteritis and acute diarrhoea among children younger than 5 years. Pooled results were extracted and analysed in STATA version 12.0 using random-effects for statistical test for homogeneity following the guidelines provided in the Cochrane Collaboration and Preferred reporting items for systematic reviews and meta-analyses. Overall, viruses accounted for 50.2% of the cases followed by bacteria with 31.6% of the cases. Parasites accounted for 12.1% of the case. Rotavirus was the most common cause of acute diarrhoea in all regions resulting in 29.2% of the cases followed by E. coli (15.6%) of diarrhoeal cases and Adenovirus (10.8%). The most prevalent parasite detected was Giardia lamblia (7.3%). Acute diarrhoea remains rampant with Rotavirus still being the major pathogen responsible for the disease in children less than 5 years old despite the introduction of vaccine. It is recommended that the vaccine should be promoted much more widely in the region.